The formulation of carvedilol transdermal patch with resin gum as rate control - Yati, Kori; Pamungkas, Septiana Tri (Pharmaciana, 2018)
Carvedilol is widely prescribed for long-term hypertension treatment. It is rapidly absorbable by oral administration, but its bioavailability is merely about 20% in humans. Drug delivery is therefore imperative to overcome this weakness. One form of transdermal drug delivery system is a patch. Transdermal patch is composed of various systems, for instance, a reservoir that uses a rate control layer to manage the rate of drug release. This research aimed to observe the effect of using resin gum as the control of drug release rate on the physical characteristics and release of carvedilol in a transdermal patch. The patches were prepared in 5 formulas with different quantities of resin gum, namely 50, 100, 150, 200, and 250 mg. Afterward, they were evaluated physically, and their dissolution and diffusion rates were analyzed. The results showed that resin gum with concentrations of 150 mg and 200 mg was physically qualified for rate control. Besides, the results of dissolution and diffusion tests revealed that transdermal patches with 150 mg of resin gum exhibited the best drug release and penetration.